2007
DOI: 10.1037/0893-164x.21.2.194
|View full text |Cite
|
Sign up to set email alerts
|

Association between alcohol intoxication and alcohol-related problems: An event-level analysis.

Abstract: Heavy drinking students experience a myriad of alcohol-related negative consequences. Use of eventlevel data permits predictions to be made regarding (a) the likelihood of alcohol-related consequences occurring after specific drinking events, and (b) moderators of the association between intoxication and consequences. College students (N = 183, 64% female) completed four consecutive 7-day drinking diaries and turned them in weekly. The diaries yielded prospective event-level data on daily drinks, time spent dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
79
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(87 citation statements)
references
References 47 publications
6
79
1
Order By: Relevance
“…Rather, these results provide empirical evidence for suggestions by Greenbaum and colleagues [6], that those who do not normally drink heavily and have lower tolerance may be especially at risk on occasions where they drink much more than they would normally. The present findings are also consistent with Neal & Carey's [7] findings that average intoxication moderated the association between daily drinking and negative consequences, such that lighter drinkers were at greater risk for negative consequences than heavier drinkers. Furthermore, Neal & Fromme [8] found that the association between alcohol use and behavioral risks increased among college students as their level of intoxication reached above their average level of intoxication.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Rather, these results provide empirical evidence for suggestions by Greenbaum and colleagues [6], that those who do not normally drink heavily and have lower tolerance may be especially at risk on occasions where they drink much more than they would normally. The present findings are also consistent with Neal & Carey's [7] findings that average intoxication moderated the association between daily drinking and negative consequences, such that lighter drinkers were at greater risk for negative consequences than heavier drinkers. Furthermore, Neal & Fromme [8] found that the association between alcohol use and behavioral risks increased among college students as their level of intoxication reached above their average level of intoxication.…”
Section: Discussionsupporting
confidence: 81%
“…However, research suggests that this may be especially true for lighter drinkers. For example, Neal and colleagues [7,8] found that average intoxication moderated the association between alcohol consumption and negative consequences such that lighter drinkers were at greater risk for negative consequences than heavier drinkers.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Wills and colleagues (2008) operationalized "good self-control" as a combined measure of planning and problem solving, and found that high levels of this trait reduced the effect of risk factors such as peer use and family events on frequency of cigarette, alcohol, and marijuana use in adolescents. Related findings have been observed in a daily diary study of college students (Neal & Carey, 2007), in which higher scores on the Eysenck Impulsiveness Scale (Eysenck, Pearson, Easting, & Allsopp, 1985)-a broad measure of acting without forethought and making hasty decisions -enhanced the relation between daily intoxication and the likelihood of experiencing consequences as a result of drinking. In a more recent study examining premeditation -or the tendency to think before acting -as a moderator, higher levels of the trait buffered the effect of depressive symptoms in predicting levels of alcohol problems, and enhanced this relation at low levels of premeditation (King et al, 2011).…”
Section: Impulse Control As a Moderatormentioning
confidence: 75%
“…Studies have shown that the relationship between drinking and consequences is imperfect, typically leaving 40%-50% of the variance unexplained (Larimer et al, 2004;Mallett et al, 2011;Turner et al, 2000). Although drinking is consistently and positively associated with consequences, studies have demonstrated that alcohol-related consequences are multi-determined and influenced by additional factors (Benton et al, 2006;Mallett et al, 2013;Neal & Carey, 2007;Turrisi et al, 2000). Specifically, Mallett and colleagues (2011) found that students' willingness to experience consequences significantly predicted consequences after controlling for drinking.…”
mentioning
confidence: 99%